In amongst the glitter and the squashed blueberries: crafting a collaborative lens for children's literacy pedagogy in a community setting. (2nd January 2017) - Hackett, Abigail; Pahl, Kate; Pool, Steve
ABSTRACT: In this article, we bring together relational arts practice (Kester, 2004) with collaborative ethnography (Campbell and Lassiter, 2015) in order to propose art not as a way of teaching children literacy, but as a lens to enable researchers and practitioners to view children's literacies differently. Both relational arts practice and collaborative ethnography decentre researcher/artist expertise, providing an understanding that "knowing" is embodied, material and tacit (Ingold, 2013). This has led us to extend understandings of multimodal literacy to stress the embodied and situated nature of meaning making, viewed through a collaborative lens (Hackett, 2014a; Heydon and Rowsell, 2015; Kuby et al, 2015; Pahl and Pool, 2011). We illustrate this approach to researching literacy pedagogy by offering a series of "little" (Olsson, 2013) moments of place/body memory (Somerville, 2013), which emerged from our collaborative dialogic research at a series of den building events for families and their young children. Within our study, an arts practice lens offered a more situated, and entwined way of working that led to joint and blurred outcomes in relation to literacy pedagogy.